Impacts of different rice-fish-prawn culture systems on yield of rice, fish and prawn and limnological conditions - Nahar, Ashfaqun (Journal of the Bangladesh Agricultural University, 2010)
An experiment was conducted to determine the impact of fish and prawn culture on some physicochemical parameters of water, weeds, benthos, and rice yield under simultaneous method for a period of 5 months from July to November 2007. The experiment was comprised of five individual treatments having three replicates for each. The treatments were: rice combined with fish and regular urea fertilization (treatment ?, T1), rice combined with prawn and regular urea fertilization (treatment ?I, T2), rice combined with fish and supplementary feeding (treatment ?II, T3), rice combined with prawn and supplementary feeding (treatment ?V T4) and treatment V (T5) was kept as control i.e., without fish and prawn. The physico-chemical parameters of water were monitored at weekly interval and were within the suitable range for fish culture. Among the treatments evaluated, the highest number of zoobenthos (worms, chironomids) was recorded in T5 without fish (control) and the lower number of the same was obtained in rice-fish culture treatments (T1 and T3) than the other treatments, indicating higher feeding preference of common carp and tilapia on zoobenthos. However, significant abundance of the weed biomass was observed in the rice-prawn farming treatments (T2 and T4) and also in control treatment. The net fish yield in T1, T2, T3 and T4 were 314.32±222.14 kg/ha, 30.98±40.86 kg/ha, 440.14±79.81 kg/ha and 81.92±62.83 kg/ha, respectively. The highest yield was recorded in T3 than the rest of the treatments. The yield was significantly higher in rice-fish treatments than those in the rice-prawn plots. Based on the results of the study, it can be suggested that the treatments with fish may be recommended for dissemination to rural farmers considering higher yields and economic benefits. Keywords: Water quality; Rice-fish; Rice-prawn; Zoobenthos; Weeds; Yields DOI: 10.3329/jbau.v8i1.6416 J. Bangladesh Agril. Univ. 8(1): 179-185, 2010